Mengoptimalkan Kemandirian Mahasiswa dalam Menyelesaikan Projek Akhir melalui Penerapan Metode Project Base Learning - Tri Kuncoro (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The aims of this study were to develop students’ antonomous learning and to equip lecturers with the knowledge of Project-Based Learning (PBL). Using a qualitative, participatory design, this study involved student taking final projects and lecturers supervising the students. PBL was found to be effective in helping students determine topics for projects, examine the practical and theoretical significance of the project, develop project timeline, select relevant methodology, and utilize relevant literature.